2019
DOI: 10.1109/access.2019.2948399
|View full text |Cite
|
Sign up to set email alerts
|

What the Fog? Edge Computing Revisited: Promises, Applications and Future Challenges

Abstract: Edge computing brings computing and storage resources closer to (mobile) end users and data sources, thus bypassing expensive and slow links to distant cloud computing infrastructures. Often leveraged opportunistically, these heterogeneous resources can be used to offload data and computations, enabling upcoming demanding applications such as augmented reality and autonomous driving. Research in this direction has addressed various challenges, from architectural concerns to runtime optimizations. As of today, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 274 publications
(331 reference statements)
0
27
0
Order By: Relevance
“…The potentialities of adopting edge computing paradigms in a broad sense were pointed out [ 33 ], while the benefits in the ambit of smart cities frameworks were widely discussed in the survey [ 34 ]. Applying edge computing in LPWAN (e.g., LoRa based ones) whose nodes have limited computational capabilities is challenging but there exist studies which proved the feasibility and indicated the benefits [ 35 ].…”
Section: Related Workmentioning
confidence: 99%
“…The potentialities of adopting edge computing paradigms in a broad sense were pointed out [ 33 ], while the benefits in the ambit of smart cities frameworks were widely discussed in the survey [ 34 ]. Applying edge computing in LPWAN (e.g., LoRa based ones) whose nodes have limited computational capabilities is challenging but there exist studies which proved the feasibility and indicated the benefits [ 35 ].…”
Section: Related Workmentioning
confidence: 99%
“…The main motivation of this work is to identify the pitfalls in cloud video synthesis to process large-volume of data to avoid latency in critical applications [11] [12]. Cloud computing aims enormous resources that can be flexibly used to fit dynamic demands which leads to avoid substantial latencies when using services placed at distant locations [9], [10] 3.WORKING PRINCIPLE There are Three Different Sections to be discussed…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fog Computing [10], also known as Edge computing [43], extends the Cloud Computing paradigm to the "Edges" of the network, bringing in new opportunities to explore applications and services. By assisting the placement of storage and data processing closer to the data sources, Edge Computing brings in benefits in terms of latency and energy consumption [44]- [48], for instance.…”
Section: B the Role Of Edge/fog Computingmentioning
confidence: 99%